Multifractal Analysis of Singularly Continuous Probability Measures - Torbin, H. M. (Ukrains’kyi Matematychnyi Zhurnal, 2005)
We analyze correlations between different approaches to the definition of the Hausdorff dimension of singular probability measures on the basis of fractal analysis of essential supports of these measures. We introduce characteristic multifractal measures of the first and higher orders. Using these measures, we carry out the multifractal analysis of singular probability measures and prove theorems on the structural representation of these measures.